A study on unsafe act, unsafe condition and communication barrier for fall from height accident in construction industry - Othman, Siti Ummi Sarah (2020)
Malaysian construction industry growth is expected to fluctuate since it was announced by the Finance Minister as part of the infrastructure project for Malaysian Budget 2020. In Malaysia, construction industry is one of the sectors which contribute to fall from height accidents. It is one of the important issues that need to be addressed by every organization in order to understand the impacts on the organizations including the workers. Currently, fall from height accidents is a challenge that many organizations struggle to overcome. Thus, to gain better understanding, this study identifies the factors that influence fall from height accidents. The main purpose of this study is to investigate the safety problem when working at height in construction site, to identify the factors that cause fall from height accidents and to analyze the factors that influence the accident and the prevention. For data collection, 264 set of questionnaires were distributed to 12 different construction sites with two (2) target levels which is supervisors and site workers. The data collected were analyze using SPSS Version 26 and the result gain through analysis of Pearson correlation and Multiple regression indicated that unsafe act, unsafe condition and communication barrier have positive relationship with fall from height accident. These finding provides useful information to the organization regarding their employees’ well-being. Besides that, it helps to enhance the underpinning theory in this study which is Accident Causation Model.